Mast cells, basophils and B cell connection network. Issue 1 (January 2015) - Merluzzi, Sonia; Betto, Elena; Ceccaroni, Alice Amaranta; Magris, Raffaella; Giunta, Marina; Mion, Francesca
Highlights B/MC and B/basophil interactions: connection between innate and adaptive immunity. MCs and basophils regulate antibody class switching and production in B cells. MC/basophil co-stimulatory molecules and soluble mediators act together to induce optimal B cell activation. MCs and basophils sustain the malignant clone expansion in B cell lymphoproliferative diseases through immune regulation functions.